2019
DOI: 10.13057/asianjagric/g030105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of container and potting media on raising quality seedlings of Acacia auriculiformis in the nursery

Abstract: Abstract. Islam MDA, Rahman MDA, Hossain MK. 2019. Effect of container and potting media on raising quality seedlings of Acacia auriculiformis in the nursery. Asian J Agric 3: 26-32. The study elucidates the effect of container and potting media on raising quality seedlings of Acacia auriculiformis in the nursery of the Institute of Forestry and Environmental Sciences, University of Chittagong to find out a suitable container and potting media for raising large scale quality seedlings. The seedlings were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…This was a common result due to the available of nutrient, water and space was higher in bigger container, and therefore will drive to increase the growth rate of seedling. This fact was agree to the several previous studies in other tree species such as Acacia nilotica, Terminalia bellirica A. auriculiformis and Cyclocarya paliurus [11], [12], [20], [21].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This was a common result due to the available of nutrient, water and space was higher in bigger container, and therefore will drive to increase the growth rate of seedling. This fact was agree to the several previous studies in other tree species such as Acacia nilotica, Terminalia bellirica A. auriculiformis and Cyclocarya paliurus [11], [12], [20], [21].…”
Section: Resultssupporting
confidence: 93%
“…The part of seedling production technology is about the selection of growing medium and its containers. These parts is important due to could determine the growth and quality of seedling and the required time to obtain the plantable seedling [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The longest primary root (31.07 cm), maximum number of secondary roots (100.72), and fresh root weight (17.55 g) was in the 4200 CC container (polybag 23 cm x 28 cm) which was statistically superior to remaining container sizes (Kishor & Ram, 2019). Another study by Islam et al (2019) indicated that the longest shoot length (137.5 cm), root length (38.1 cm), and collar diameter (9.5 mm) were highest in T4 treatment which had the largest potting tube size (20 x 25 cm). Studies have shown that soil fertility and water retention are also positively correlated with potting tube size (Islam et al, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…Another study by Islam et al (2019) indicated that the longest shoot length (137.5 cm), root length (38.1 cm), and collar diameter (9.5 mm) were highest in T4 treatment which had the largest potting tube size (20 x 25 cm). Studies have shown that soil fertility and water retention are also positively correlated with potting tube size (Islam et al, 2019). A study by Agonafer et al, (2016) found that larger pots retained more water than smaller ones; this has important implications for seedlings development in drylands, where water is scarce.…”
Section: Introductionmentioning
confidence: 96%
“…The use of suitable growing media or substrates for sowing of seeds directly affects the germination, development and functional rooting system. A good growing medium provides sufficient anchorage or support to the plant, serves as reservoir for nutrients and water, allow oxygen diffusion to the roots and permit gaseous exchange between the root and atmosphere outside the root substratem [7][8][9][10]. The quality of seedlings is very much influenced by growing media under nursery.The quality of seedlings obtained from a nursery influences reestablishment in the field and the eventual productivity of an orchard [11].…”
Section: Introductionmentioning
confidence: 99%